The staircase [videorecording (DVD)] - Campos, Antonio, 1983- (SDS : Warner, 2022)
Inspired by a true story, The Staircase follows writer and war veteran Michael Peterson after the suspicious death of his wife Kathleen. On December 9, 2001, Michael makes a frantic 911 call reporting Kathleen has fallen down the stairs of their Durham, NC home. But when the district attorney brings murder charges, members of Michael's blended family must choose whose side they're on and which version of events to believe. As the case becomes engulfed in a media circus, a French documentary film crew arrives to meticulously chronicle its many twists and turns. Intertwining multiple perspectives and timelines, this gripping limited series explores the elusive nature of truth, while serving as an intimate portrait of a family's grief.